Controls on and geological models of hydrocarbon accumulation in gentle slopes caused by exceptionally weak tectonic activities: A case study of the Lixian Slope, Raoyang Sag, Eastern China. (June 2022) - He, Fugui; Gao, Xianzhi; Yang, Dexiang; Fan, Bingda; Ren, Changqing; Guo, Huiping; Wang, Huilai; Huang, Yuanxin
Abstract: The Lixian Slope is located in the western part of the Raoyang Sag, Bohai Bay Basin, Northern China. This slope was developed due to exceptionally weak tectonic activities; therefore, it is aptly called a weak tectonic slope. The slope gradients, faults, sandbodies, source rocks, and oil-source correlation were evaluated. During the development of the Lixian Slope, its gradients were usually low (generally less than 1.00°). Most of the faults have low fault throws (usually less than 30 m). Moreover, the faults of this slope have poor vertical transporting capacity. The sandstone-to-strata ratios for different Paleogene strata of the Lixian Slope are generally less than 40%, suggesting that the connectivity of sandbodies in the Paleogene strata is poor. In addition, research on the sources of crude oil indicates that the oil in most slope areas originated from Es1x source rocks. The study of the controls on hydrocarbon accumulation in the Lixian Slope indicates the following: 1) the planar distribution of oil and gas reservoirs in the Lixian Slope is strictly controlled by both the Es1x and Ek–Es4 source rocks, the Es1x in particular; 2) the sandbodies, faults, and low gradients control the planar enrichment of hydrocarbons; and 3) the faults and source rocks control the vertical distribution of oil and gas reservoirs. According to the characteristics of and controls on hydrocarbon accumulation, a hydrocarbon accumulation model suitable for a weak tectonic slope is proposed. Finally, a few recommendations for future explorations are suggested. The Es2 and Es1 members, especially those near the NNE–NEE trending faults, are critical target intervals for future exploration operations. Highlights: Fault function in the migration and accumulation of oils in weak tectonic slope. Connectivity and transporting capacity of sandbody in weak tectonic slope. Vertical distribution of oil-gas reservoirs is mainly controlled by the faults and source rocks. Sandbodies, faults and low gradients control the planar enrichment of hydrocarbons. Representative hydrocarbon accumulation models in weak tectonic slope.